Pengendalian Kualitas Produk Spon Kasur Menggunakan Exponentially Weighted Moving Average (Ewma) pada UD. Celcius Gegutu Timur - Lingking, Fransiska Prisilia; Harsyiah, Lisa; Sulistyowati, Emmy Dyah; Asri, Adis Tia Juli Agil (Semeton Mathematics Journal, 2025)
Problems that arise at UD. Celsius, one of the manufacturers of sponge mattress products in the East Gegutu area, said that differences in product weight will cause a decrease in product quality. Consequently, here, quality is of primary concern. Because the Exponentially Weighted Moving Average (EWMA) control chart can detect small average changes, this study aims to examine the quality control of mattress sponge products using this chart. The information used relates to the mass of a mattress sponge product measuring 160×120×25 cm, with four variables, namely X_1,X_2,X_3 and X_4, Quality control in this research uses a weighting factor value of  = 0.4. Based on the research results, the assumption that is not fulfilled is the assumption of data randomness, so that the EWMA control chart pattern formed shows that the data is not statistically controlled. However, there is no data that is out of control, so in this study the Average Run Length (ARL) value of 27,204 indicates that there will be data that is first out of control, namely the 27th or 28th data. And the results of the capability analysis of the process show that the production process is not capable because the values of Cp=0.3432 and Cpk=0.3373 where the values of Cp,Cpk<1, this is due to the influencing factors, namely man, machine, material and method factors.